Comparative Study Between Aluminum Monolith and Foam as Carriers for The Intensification of The CO Water Gas Shift Process - Vincenzo Palma (Catalysts, 2018)
A comparison between the effect of different highly thermal conductive carriers on the performance of Pt/CeO2/Al2O3-based structured catalysts in a water⁻gas shift reaction, was reported. The structured catalysts were prepared by means of washcoating two carriers, a flow through aluminum monolith and an open cell aluminum foam, with the same contact surface and the same chemical composition of the washcoat. The experiments were carried out under stressful conditions (no dilution and high space velocity), so as to minimize the thermal dispersions and to highlight the effect of the thermal conductivity of the carriers and the material transport phenomena. Both of the catalysts showed a substantially flat thermal profile, while the carbon monoxide conversion was higher with the foam-based catalyst, as a result of the higher temperatures reached. The experimental results were validated with a computational fluid dynamics (CFD) simulation by using the finite elements software, COMSOL Multiphysics®. Through the simulation results, it was also possible to investigate the effects of transport phenomena on the two catalytic systems, such as mass and heat transfer.